Considerations for test design to accommodate energy‐budget models in ecotoxicology: A case study for acetone in the pond snail Lymnaea stagnalis. (2nd May 2014) - Barsi, Alpar; Jager, Tjalling; Collinet, Marc; Lagadic, Laurent; Ducrot, Virginie
Abstract Toxicokinetic–toxicodynamic (TKTD) modeling offers many advantages in the analysis of ecotoxicity test data. Calibration of TKTD models, however, places different demands on test design compared with classical concentration–response approaches. In the present study, useful complementary information is provided regarding test design for TKTD modeling. A case study is presented for the pond snail Lymnaea stagnalis exposed to the narcotic compound acetone, in which the data on all endpoints were analyzed together using a relatively simple TKTD model called DEBkiss. Furthermore, the influence of the data used for calibration on accuracy and precision of model parameters is discussed. The DEBkiss model described toxic effects on survival, growth, and reproduction over time well, within a single integrated analysis. Regarding the parameter estimates (e.g., no‐effect concentration), precision rather than accuracy was affected depending on which data set was used for model calibration. In addition, the present study shows that the intrinsic sensitivity of snails to acetone stays the same across different life stages, including the embryonic stage. In fact, the data on egg development allowed for selection of a unique metabolic mode of action for the toxicant. Practical and theoretical considerations for test design to accommodate TKTD modeling are discussed in the hope that this information will aid other researchers to make the best possible use of their test animals. Environ Toxicol Chem 2014;33:1466–1475. © 2014 SETAC